COMPOUNDS AND SPEECH INSERTS (In the example of the works of Azod Sharafiddinov) (Scientific journal of the Fergana State University, 2026)
Although inserted constructions originally entered the literary language from oral and colloquial speech, the contemporary written Uzbek literary language demonstrates the emergence of new semantic and structural types of such constructions, their widespread use across all genres and styles, and the expansion of their functional scope. This phenomenon is, of course, associated with the remarkable development of the modern Uzbek literary language. The present article aims to analyze the specific features of insertions found in the works of O. Sharafiddinov.